Perspectives on childhood resilience among the Aboriginal community: an interview study - Christian Young; Allison Tong; Janice Nixon; Peter Fernando; Deanna Kalucy; Simone Sherriff; Kathleen Clapham; Jonathan C. Craig; Anna Williamson (Elsevier, 2017)
Abstract Objective: To describe Aboriginal community members' perspectives on the outcomes and origins of resilience among Aboriginal children. Methods: Face‐to‐face interviews were conducted with 36 Aboriginal adults (15 health service professionals, 8 youth workers and 13 community members) at two urban and one regional Aboriginal Community Controlled Health Service in New South Wales. Interviews were transcribed and analysed thematically. Results: We identified six themes: withstanding risk (displaying normative development, possessing inner fortitude); adapting to adversity (necessary endurance, masking inner vulnerabilities); positive social influences (secure family environments, role modelling healthy behaviours and relationships); instilling cultural identity (investing in Aboriginal knowledge, building a strong cultural self‐concept); community safeguards (offering strategic sustainable services, holistic support, shared responsibility, providing enriching opportunities); and personal empowerment (awareness of positive pathways, developing self‐respect, fostering positive decision making). Conclusions: Community members believed that resilient Aboriginal children possessed knowledge and self‐belief that encouraged positive decision making despite challenging circumstances. A strong sense of cultural identity and safe, stable and supportive family environments were thought to promote resilient behaviours. Implications for public health: Many Aboriginal children continue to face significant adversity. More sustainable, Aboriginal‐led programs are needed to augment positive family dynamics, identify at‐risk children and provide safeguards during periods of familial adversity.